The Development of Compact Vertical Axis Wind Turbine: The Feasibility Study for Applying the twisted blade VAWT with an Air Conditioner’s Condensing Unit - Rerkkumsup, Pongpun; Aramwanid, Patiparn; Yaruan, Panurut (Journal of Advanced Development in Engineering and Science, 2023)
This research describes the feasibility study for applying the twisted blade savonius wind turbine to generate electrical energy using a condensing unit of air conditioner as wind energy source. The vertical axis wind turbine with diameter of 70 centimeters and height of 70 centimeters is simulated in SolidWorks® Flow Simulation to study the wind speed that impacted to modeled wind turbine. The simulation results show that wind speed from condensing unit is suitable for the operation of VAWT. Two VAWTs are constructed using inhouse and easy to find materials for studying electrical energy generation. The experimental testing results of wind speed at different adjustable distances between VAWT and condensing unit, and transverse distances between air outlet and VAWT show that the distance between VAWT and condensing unit is the important factor for wind speed significantly more than the transverse distance. The second VAWT, that is weight reduced by 66.4% from the first prototype, can generate the maximum electrical voltage of 16.2 V at wind speed of 5.9 m/s, in which approximately 4 times higher than generated by the first prototype VAWT. The results of feasibility studied illustrate that the twisted blade savonius wind turbine can be used with a condensing unit to generate electrical energy in satisfied level.